Membangun Citra Merek Melalui Promosi Penjualan Dan Penggunaan Media Sosial Instagram Serta Implikasinya Terhadap Loyalitas Pelanggan: Studi Empiris Konsumen Tomoro Coffee - Sujana Sujana; Salfa Sa’adatul Rahmaniah; Saefudin Zuhdi; Bambang Hengky Rainanto; Febry Lodwyk Rihe Riwoe (Jurnal Ilmiah Pariwisata Kesatuan, 2026)
The development of digital technology and changes in consumer lifestyle have encouraged F&B companies to be more proactive in promoting and building their brands, especially through social media platforms such as Instagram. This study aims to: (1) Examine the effect of sales promotion on the brand image of Tomoro Coffee; (2) Examine the effect of Instagram social media usage on the brand image of Tomoro Coffee; (3) Examine the effect of sales promotion on customer loyalty; (4) Examine the effect of Instagram social media usage on customer loyalty; (5) Examine the effect of brand image on customer loyalty. This research adopts a quantitative approach using a survey method by distributing questionnaires to 240 respondents who are Tomoro Coffee consumers in the JABODETABEK area. The sampling technique used is purposive sampling, and the data were analyzed using the Structural Equation Modeling (SEM) method with the assistance of AMOS software. The results show that: (1) Sales promotion has a positive and significant effect on brand image; (2) Instagram social media usage has a positive and significant effect on brand image; (3) Sales promotion has a positive and significant effect on customer loyalty; (4) Instagram social media usage has a positive and significant effect on customer loyalty; and (5) Brand image has a positive and significant effect on customer loyalty. In conclusion, each variable examined contributes positively to the development of brand image and the improvement of customer loyalty toward the Tomoro Coffee brand. Keywords: Sales Promotion, Instagram Social Media, Brand Image, Customer Loyalty